A contribution to the knowledge of Amanita coryli (Amanitaceae, Agaricales) - Fuat Bozok; Boris Assyov; Mahmut Yarar; Hatıra Taşkın (Botanica Serbica, 2023)
The authors present descriptions and illustrations of Amanita coryli, rarely featured in the mycological literature, based on molecularly characterised by nrITS sequences specimens from the Balkan Peninsula (Bulgaria and Turkey). The collections studied here suggest that the species is probably not restricted to the presumed host-trees of the genus Corylus and may also occur with some Fagaceae. Further, the analysis of previously released sequences in public databases show that it is a species with a wide distribution in Eurasia, probably much more common than currently known, but likely confused with other members of the section Vaginatae